Challenges to attain extreme measures for patient safety clinical governance and care of the national core standards for health establishments in a district hospital in Tswane Gauteng - Du Plessis, Moselene Annelene Rosemary (University of Pretoria, 2019)
Dissertation (MCur)--University of Pretoria, 2018.